Pathological effects of pregabalin toxicity in rats - Roaa Salih Mahdi; Nawras Najah; Sura Salman Ejam (Medical Journal of Babylon)
Abstract Background: Pregabalin (PGB) is one kind of gabapentinoid. The main mechanism of action is binding at the alpha-2-delta site, which inhibits calcium influx in response to depolarization at nerve terminals and, in turn, suppresses the release of glutamate, noradrenaline, and substance P. Objectives: This study aimed to study the pathological effects of PGB toxicity on brain and liver of rats. Materials and Methods: We chose 20 mature albino rats, both sexes, averaging 220 g in weight; these were divided into two groups (10 rats per group): the toxic group and the control group. Tablets of Lyrica (Pfizer) may be purchased over the counter. The 300 mg of PGB in each tablet was dissolved in 3 mL of 0.9% normal saline. The dosage was determined using the maximum lethal oral dose in rats (5000 mg/kg) (Pfizer, 2017). Based on the rats’ weights, a toxic dosage of 1000 mg of PGB was determined and reconstituted in normal saline (0.9% in 3 mL). Each animal in the acute toxicity group received a single dose of the produced medication orally. After 24 h, all of the animals in both groups were euthanized. The brain and liver were quickly dissected and removed, washed in saline solution, and then processed for histopathological study. Results: Focal regions of hemorrhage and congestion were seen in H&E-stained sections from the acute toxicity group, and most pyramidal cells were degraded, pyknotic, and exhibited karyolysis. Cerebellar cortical layers were preserved; however, Purkinje cells were destroyed in the acute toxicity group, which also exhibited an increase in pyknotic cells, hemorrhage, vascular congestion, and localized loss of tissue. Hemorrhages, congestion of portal region blood vessels, and central veins and hepatic sinusoids were some of the most notable pathological abnormalities seen in the livers of those using PGB. Hepatocytes show nuclear pyknosis and a homogeneously acidophilic cytoplasm as a result of severe degenerative alterations, such as vacuolar degeneration and severe necrotic changes. Conclusion: PGB can cause pathological lesions in the brain and liver at a single toxic dose.